2020
DOI: 10.3390/ma13163460
|View full text |Cite
|
Sign up to set email alerts
|

Application of DIC Method in the Analysis of Stress Concentration and Plastic Zone Development Problems

Abstract: The paper presents the assessment of the possibility and reliability of the digital image correlation (DIC) system for engineering and scientific purposes. The studies were performed with the use of samples made of the three different materials—mild S235JR + N steel, microalloyed fine‑grain S355MC steel, and high strength 41Cr4 steel subjected to different heat‑treatment. The DIC studies were focused on determinations of dangerous zones with large stress concentrations, plastic deformation growth, and predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…Cerbu et al have successfully used this technique to characterize the mechanical response of glass fiber composites [12], while Dudescu et al [13] have determined the thermal expansion coefficient of polypropylene and polyvinylchloride. Romanowicz et al [14] have shown the DIC capability of determining stress concentration factors on samples fabricated from ductile materials. They have proven the viability of the method by obtaining comparable results between DIC techniques and FEM analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Cerbu et al have successfully used this technique to characterize the mechanical response of glass fiber composites [12], while Dudescu et al [13] have determined the thermal expansion coefficient of polypropylene and polyvinylchloride. Romanowicz et al [14] have shown the DIC capability of determining stress concentration factors on samples fabricated from ductile materials. They have proven the viability of the method by obtaining comparable results between DIC techniques and FEM analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue failures are caused by random, repetitive, or cyclic loads that are generally significantly lower than loadings that would lead to the plastic deformation of the material. The onset of fatigue cracks may occur due to material imperfections, structural discontinuities, or stress concentrators [ 3 , 4 , 5 , 6 , 7 , 8 ]. The applied fatigue loads may be uniaxial (with one stress component), biaxial (with two stress components), or multiaxial (with more than two stress components) [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the rapid development of computer technology has promoted the gradual maturity of 3D digital technology. The digital image correlation (DIC) technology used for measuring surface deformities has the characteristics of "non-contact" [12,13] and "full-field" [14][15][16] displacement information on the surface. It is the most promising 3D data acquisition method in current engineering applications and can be used to measure tensile mechanical properties of welding joints.…”
Section: Introductionmentioning
confidence: 99%